Method of Ventral Hernia Repair: Our Experience (Medico Legal Update, 2021)
Background: Ventral hernias result from weakness in the musculofascial layer of the anterior abdominalwall. Ventral hernia can be operated through open or laparoscopic approach. Moreover, there are variousoptions available for mesh placement during the repair. We here report our experience in surgical managementof ventral hernias along with review of published literature along with laparoscopic repair of ventral hernias.Method: It was a retrospective study of patients who were operated for ventral hernias over a period of 4years in a teaching hospital of Vadodara SBKS research institute Dhiraj Hospital. All patients irrespective ofage and sex were included. All patients were evaluated by obtaining proper history and performing detailedphysical examination and routine blood investigations. Various intra operative and postoperative parameterswere observed and reported.Conclusions: The ventral hernia repair can be done by open and laparoscopic technique. Each has its ownadvantages and disadvantages. There is no conclusively guidelines about the superiority of one techniqueover the other and also no conclusively guidelines for the proper position of mesh placement. The clearadvantages of open technique is avoidance of general anesthesia in many cases (as many ventral herniarepairs can be done under local anaesthesia), lesser learning curve, cheap meshes can be used, easy tolearn, no requirement of any sophisticated instruments or OT setup and trained staff. The disadvantage oflaparoscopic technique includes the requirement for general anaesthesia (as many ventral hernias can beperformed with local anaesthesia in open technique), need to transverse the abdominal cavity, prolongedlearning curves, requirement of costly meshes and sophisticated equipment and technical staff. However,laparoscopy has advantage over open hernia repair in terms of reduced postoperative pain, decreasedpostoperative complications, reduced length of hospital stays, less time for return to normal activity andbettercosmesis.